The role of public sector expenditure on local economic development. (2016) - Khusaini, Mohamad
This research aims at analysing the effect of public sector expenditure on local economic development in East Java Province, Indonesia. Using path analysis, the result showed that public sector expenditure has a direct positive effect on local economic development. However, not all public sector expenditure indicators have an indirect effect on local economic development. Indirect effect occurs between public sector expenditure on local economic development through spending on education and health sectors, while infrastructure sector expenditure has no significant effect indirectly on local economic development. That is to say that the increase in public sector expenditure tends to increase economic growth through local economic development indicators in education and health, but not through the indicators of local development in infrastructure.